The Effects of Disease on the London Missionary Society’s South Seas Missions between 1797 and 1860 - Alden, Jonny (Social sciences and missions, 2018)
European missionary activity enabled not only the communication of the Christian message, but facilitated the dissemination of a mélange of diseases amongst epidemiologically disparate cultural groupings. This paper explores the influence of disease upon the London Missionary Society’s South Seas missions between 1797 and 1860. I argue that disease shaped missionary activity in three central ways: Firstly, through shaping missionaries’ primary experiences; secondly, through moulding the ways in which native peoples conceptualised and responded to the Christian message; and finally, through contributing profoundly towards missionary conceptions of European superiority and the Polynesian ‘other’.